Integration model of control of lifelong education system in educational clusters and mechanisms of network interaction - Dmitrij E. Ovchinnikov; Ekaterina P. Aсri; Elena P. Schegoleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Today, in conditions of uncertainty and a high level of competitiveness in the labor market, it is necessary to conduct high-quality training of professional personnel in secondary vocational and higher education in a shorter time. A two-level system of training on one educational platform allows you to maintain the continuity of the content of educational programs. The integration process in the field of education makes it possible to achieve high positive results through the diffusion of differentiated elements and properties into a single professional educational space. The paper considers the main directions of integration processes in the framework of continuing education in the format of educational clusters on the example of a University. This model makes it possible to improve the quality and efficiency of training highly qualified personnel for an intensively developing labor market. The implementation of the integration model of management of the system of continuing education through the mechanism of interaction of educational programs of secondary vocational education and higher education creates a collaborative educational environment, which allows to provide the labor market with qualified personnel in the shortest possible time. A variant of the interaction of the integration model of the functioning of the training of middle-level and higher specialists on the platform of the federal state budgetary educational institution of higher education Samara State Technical University is considered.